The experience of informal caregiving within Saudi society: expressed needs and expectations - Soha Almehmadi; Abeer M. Alrashed (SpringerOpen, 2023)
Abstract Background Even though informal caregivers have always been a major element within any society, their contribution to the healthcare system has only recently been recognized. Accordingly, the sustainability of their informal social role is becoming a major concern to policymakers. In Saudi Arabia, recognition of informal caregiving is still limited. This study was carried out to investigate the experience of caregiving in informal settings through identifying the needs of the caregivers along with their expectations of the formal system. Methods A cross-sectional study was conducted to measure the experience of Saudi informal caregivers who were caring for at least one individual with a dependency resulting from either disability, aging, or both. A self-administered questionnaire was designed specifically for this study with 88% reliability. A convenient sample of 300 caregivers was invited electronically through 14 websites supporting families with dependent individuals. Results Of the eligible participants (n = 271), about two-thirds were caring for one elderly person or more, while one-third were caring for individual(s) with disabilities. The two groups did not differ in their needs; their greatest perceived needs were necessary equipment for care recipients, free time to socialize, alternative care setting, and proper income. Overall, the needs on the system level were the highest, followed by the needs on the financial level, then on the social level. On the other hand, the caregivers of individuals with disabilities had greater expectations of formal support than caregivers of the elderly. The greatest expectation among the participants was facilitating care recipients' mobility within their communities. Overall, the expectations of information support were the highest followed by the expectations of financial support and then material support. Conclusion The participants expressed great expectations of formal support along with some unmet needs. Further research is recommended to emphasize the role of primary caregivers along with the nature of the assistance received throughout the caregiving process. The needs of individuals with dependencies along with those of the caregivers must be considered in the planning process of healthcare services. Finally, the expectations of informal caregivers should lead the priorities of the development decisions of long-term care services.